Denitrification in hypersaline and coastal environments - Torregrosa-Crespo, Javier; Miralles-Robledillo, Jose María; Bernabeu, Eric; Pire, Carmen; Martínez-Espinosa, Rosa María (FEMS microbiology letters, 2023)
Abstract As the association of denitrification with global warming and nitrogen removal from ecosystems has gained attention in recent decades, numerous studies have examined denitrification rates and the distribution of denitrifiers across different environments. In this minireview, reported studies focused on coastal saline environments, including estuaries, mangroves, and hypersaline ecosystems, have been analysed to identify the relationship between denitrification and saline gradients. The analyses of the literature and databases stated the direct effect of salinity on the distribution patterns of denitrifiers. However, few works do not support this hypothesis thus making this topic controversial. The specific mechanisms by which salinity influences denitrifier distribution are not fully understood. Nevertheless, several physical and chemical environmental parameters, in addition to salinity, have been shown to play a role in structuring the denitrifying microbial communities. The prevalence of nirS or nirK denitrifiers in ecosystems is a subject of debate in this work. In general terms, in mesohaline environments, the predominant nitrite reductase is NirS type and, NirK is found predominantly in hypersaline environments. Moreover, the approaches used by different researchers are quite different, resulting in a huge amount of unrelated information, making it difficult to establish comparative analysis. The main techniques used to analyse the distribution of denitrifying populations along salt gradients have been also discussed. Importance of denitrification in saline and hypersaline environments in terms of denitrification rates and expression and abundance of denitrification genes in salinity gradients.